The Role of Visum et Repertum as a Tool of Evidence in Evidence Against the Criminal Act of Persecutory (Study of Decision No. 646/Pid.B/2021/PN Rap.) - Dewi Patima Hutagalung; Risdalina Risdalina; Indra Kumalasari M (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Visa et repertumis a written explanation letter made by a doctor in forensic medical science regarding medical checks on humans, made based on his knowledge and under oath for the benefit of justice. There is also a problem formulation in this matter. 1. What are the requirements for a visum et repertum so that it can become valid evidence? 2. How is the strength of the visum et repertum as evidence in proving the case of persecution in the decision no. 646/Pid.B/2021/PN Rap? The method used in this writing is using the Juridical Normative Empirical method, namely by conducting field research with the method of interviews with related parties and library research in the form of literature books, legislation, legal articles, scientific essays, as well as other readings that are related to the problems discussed in the preparation of this article. While the problem of approach used is the Legislative approach, the Conceptual approach and the Visum et Repertum Problem approach are documentary evidence as regulated in Article 184 paragraph (1) of the Criminal Procedure Code and Article 187 letter c of the Criminal Procedure Code and has strong evidentiary power because it is able to prove elements persecution, in researching this problem the author takes an example of a case that is in accordance with the title above, namely decision no. 646/Pid.B/2021/PN Rap. The consequences that arise if the Visum et Repertum has a comparison to the explanation given by the suspect is that the explanation can be revoked and a re-check of the Visum et Repertum can be carried out if the suspect is proven to have given a wrong confession. In order for Visum et Repertum to have the power of juridical proof, it is necessary to regulate the standardization of the model and form as well as the arrangement of Visum et Repertum in a statutory regulation.